Comprehensive analysis and effective treatment of plugging in shale gas wells: From composition identification to removal agent optimization - Yujia Xiong; Jun Xin; Chao Su; Lei Liang; Qinghua Xiao; Haifeng Ye; Zilai Mei (PLoS ONE, 2025)
With the extensive exploitation of shale gas fields in southern Sichuan, China, the Weiyuan Area – a key production zone within this region – has experinced a growing gas well plugging problem, which significantly hampers production efficiency. This study presents a comprehensive analysis of plugging problems in this area. Plugging samples were obtained from typically affected gas wells and subjected to a suite of analytical techniques. Results indicated that plugging materials were predominantly inorganic, primarily comprising iron-based impurities and mineral scale deposits, while organic components—present in minor proportions—primarily composed of long-chain alkanes. The formation of these plugs is attributed to downhole corrosion, high-salinity formation water, and complex chemical interactions occurring within the wellbore. In response, specialized plugging removal agents were developed: an organic composite acid-organic solvent system achieved up to 98% dissolution efficiency for iron oxide-dominated plugs; a chelating agent based on CDTA was optimized for iron sulfide-based plugging; and the DTPA-based system exhibited superior dissolution efficiency for barium sulfate/calcium carbonate scale deposits. This research provides a scientific basis for effectively mitigating plugging issues in comparable shale gas fields.